A systematic review on concurrent aneuploidy screening and preimplantation genetic testing for hereditary disorders: What is the prevalence of aneuploidy and is there a clinical effect from aneuploidy screening?. (13th March 2020) - Toft, Christian Liebst Frisk; Ingerslev, Hans Jakob; Kesmodel, Ulrik Schiøler; Diemer, Tue; Degn, Birte; Ernst, Anja; Okkels, Henrik; Kjartansdóttir, Kristín Rós; Pedersen, Inge Søkilde
Abstract: Introduction: In assisted reproductive technology, aneuploidy is considered a primary cause of failed embryo implantation. This has led to the implementation of preimplantation genetic testing for aneuploidy in some clinics. The prevalence of aneuploidy and the use of aneuploidy screening during preimplantation genetic testing for inherited disorders has not previously been reviewed. Here, we systematically review the literature to investigate the prevalence of aneuploidy in blastocysts derived from patients carrying or affected by an inherited disorder, and whether screening for aneuploidy improves clinical outcomes. Material and methods: PubMed and Embase were searched for articles describing preimplantation genetic testing for monogenic disorders and/or structural rearrangements in combination with preimplantation genetic testing for aneuploidy. Original articles reporting aneuploidy rates at the blastocyst stage and/or clinical outcomes (positive human chorionic gonadotropin, gestational sacs/implantation rate, fetal heartbeat/clinical pregnancy, ongoing pregnancy, miscarriage, or live birth/delivery rate on a per transfer basis) were included. Case studies were excluded. Results: Of the 26 identified studies, none were randomized controlled trials, three were historical cohort studies with a reference group not receiving aneuploidy screening, and the remaining were case series. In weighted analysis, 34.1% of 7749 blastocysts were aneuploid. Screening for aneuploidy reduced the proportion of embryos suitable for transfer, thereby increasing the risk of experiencing a cycle without transferable embryos. In pooled analysis the percentage of embryos suitable for transfer was reduced from 57.5% to 37.2% following screening for aneuploidy. Among historical cohort studies, one reported significantly improved pregnancy and birth rates but did not control for confounding, one did not report any statistically significant difference between groups, and one properly designed study concluded that preimplantation genetic testing for aneuploidy enhanced the chance of achieving a pregnancy while simultaneously reducing the chance of miscarriage following single embryo transfer. Conclusions: On average, aneuploidy is detected in 34% of embryos when performing a single blastocyst biopsy derived from patients carrying or affected by an inherited disorder. Accordingly, when screening for aneuploidy, the risk of experiencing a cycle with no transferable embryos increases. Current available data on the clinical effect of preimplantation genetic testing for aneuploidy performed concurrently with preimplantation genetic testing for inherited disorders are sparse, rendering the clinical effect from preimplantation genetic testing for aneuploidy difficult to access.